(untitled) (Ustozlar uchun, 2026)
This article examines the benefits of watching English movies for language learning, focusing on listening, vocabulary, speaking skills, and psychological effects. Movies help improve listening by familiarizing learners with natural pronunciation, different accents, and fast-paced dialogues. They also expand vocabulary by providing words, phrases, idioms, and informal expressions in context, reinforced through repetition and subtitles.